2013
DOI: 10.21083/partnership.v8i1.2009
|View full text |Cite
|
Sign up to set email alerts
|

Information Seeking in Context: Results of Graduate Student Interviews

Abstract: The authors conducted a qualitative research study examining the information seeking behaviours of Psychology, Sociology, and Women's Studies graduate students at a large research intensive university to determine: how graduate students find information; the roles that faculty members, fellow graduate students and librarians play in the information search; and graduate students' knowledge of information resources and services. The context of graduate student information seeking was uncovered through an analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…For instance, Jamali and Nicholas (2006) found that doctoral students tend to use word of mouth more than more senior researchers. On the other hand, Sloan and McPhee (2013) suggest that the physical and social structure of an academic department, as well as the overall structure of the campus, may influence the relationships doctoral students develop with their fellow doctoral students, faculty and librarians. The authors found that graduate students were more likely to seek assistance from faculty or their supervisor for information about their research, while for any other type of information (like more general questions) they would consult their fellow graduate students; looking specifically at doctoral students within this group, it was found that they were less likely to seek assistance from both fellow students, faculty and librarians.…”
Section: Doctoral Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Jamali and Nicholas (2006) found that doctoral students tend to use word of mouth more than more senior researchers. On the other hand, Sloan and McPhee (2013) suggest that the physical and social structure of an academic department, as well as the overall structure of the campus, may influence the relationships doctoral students develop with their fellow doctoral students, faculty and librarians. The authors found that graduate students were more likely to seek assistance from faculty or their supervisor for information about their research, while for any other type of information (like more general questions) they would consult their fellow graduate students; looking specifically at doctoral students within this group, it was found that they were less likely to seek assistance from both fellow students, faculty and librarians.…”
Section: Doctoral Mentoringmentioning
confidence: 99%
“…Barriers that refrain doctoral students from asking help from librarians are manifold and varied. Sloan and McPhee (2013) refers to the need for instant help, uncertainty about what can be asked or late working hours. Chen and Brown (2012), on the other hand, identifies a series of reasons for which international students, and in particular Chinese students, may not want to seek help from a librarian.…”
Section: Is There a Role For Librarians?mentioning
confidence: 99%
“…The library literature on the information seeking behaviors and needs of graduate students in general is also relevant (Catalano, 2013; Sloan and McPhee, 2013; Spezi, 2016). However, there is little that focuses specifically on international graduate students (Chen and Brown, 2012; Liu and Winn, 2009; Morrissey and Given, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subject librarians have interviewed graduate students in their individual disciplines to meet their research needs (Jabbar, 2019;Moore & Singley, 2019;Sloan & McPhee, 2013). Several surveys explored ways to engage specific departments, research groups, and organizations (Fong, 2014;Fong & Hansen, 2012;Hart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%